Focal Delivery of Neurotrophins into the Central Nervous System Using Fluorescent Latex Microspheres. (November 1997) - Riddle, David R.; Katz, Lawrence C.; Lo, Donald C.
A new technique for in vivo and in vitro delivery of neurotrophins is described. The method is based upon the ability of certain fluorescent latex microspheres to adsorb large quantities of neurotrophin and then release the factor for at least three to four days. Injection of such neurotrophin-coated microspheres in vivo provides focal delivery of neurotrophins to distinct populations of neurons. The fluorescence of the microspheres accurately identifies the region of neurotrophin treatment in vivo; two independent methods indicate that microsphereborn proteins do not diffuse significantly beyond the site of injection. In addition to providing focal delivery and labeling of the site of application, labeled microspheres are retrogradely transported by neurons; thus, neurons whose distant terminals are exposed to neurotrophin can be identified and analyzed. This approach provides a powerful method for the introduction of neuroactive proteins into defined and localized regions of the central nervous system.